DNA Repair and Photoprotection: Mechanisms of Overcoming Environmental Ultraviolet Radiation Exposure in Halophilic Archaea - Jones, Daniel L.; Baxter, Bonnie K. (Frontiers in Microbiology, 2017)
Halophilic archaea push the limits of life at several extremes. In particular, they are noted for their biochemical strategies in dealing with osmotic stress, low water activity and cycles of desiccation in their hypersaline environments. Another feature endemic to their habitats is intense ultraviolet (UV) radiation, which is a challenge that microorganisms must overcome. The consequences of high UV exposure include DNA lesions arising directly from bond rearrangement of adjacent bipyrimidines, or indirectly from oxidative damage, which may ultimately result in mutation and cell death. As such, these microorganisms have evolved a number of strategies to navigate the threat of DNA damage, which we differentiate into two categories, DNA repair and photoprotection. Photoprotection encompasses damage avoidance strategies that serve as a “first line of defense,” and in halophilic archaea include pigmentation by carotenoids, mechanisms of oxidative damage avoidance, polyploidy, and genomic signatures that make DNA less susceptible to photodamage. Photolesions that do arise are addressed by a number of DNA repair mechanisms that halophilic archaea efficiently utilize, which include photoreactivation, nucleotide excision repair, base excision repair, and homologous recombination. This review seeks to place DNA damage, repair, and photoprotection in the context of halophilic archaea and the solar radiation of their hypersaline environments. We also provide new insight into the breadth of strategies and how they may work together to produce remarkable UV-resistance for these microorganisms.